Effects of dietary carbohydrate/lipid ratios on growth, body composition, and nutrient utilization of hybrid cat sh (Pseudoplatystoma reticulatum x Leiarius marmoratus) - Bernardes Célio L; Navarro, Rodrigo D; Guerra Santos, Bartira; Fortes Silva, Rodrigo (Revista Colombiana de Ciencias Pecuarias, 2016)
farming of hybrid catfish is relatively recent in Brazil; consequently, it is necessary to develop practical diet formulations for this fish. Objective: to evaluate the influence of different carbohydrate/lipid ratios (CHO:L) on growth performance, body composition and nutrient utilization of hybrid catfish (Pseudoplatystoma reticulatum x Leiarius marmoratus). Methods: four isonitrogenous diets were formulated with increasing lipid levels, using the following CHO:L ratios: 1.3:1 (diet 1); 1.1:1 (diet 2); 0.9:1 (diet 3), and 0.8:1 (diet 4). Fish were fed 5% of BW/day (dry-weight basis) in triplicate groups of 6 fish each (18 ± 1.5 g) for 2 months. Results: though final weight and absolute weight gain decreased with increasing dietary lipid (p < 0.05), there was no significant difference in daily feed consumption among treatments (p > 0.05). Moreover, viscerosomatic index and hepatosomatic index showed no statistical difference among dietary treatments. Body lipid increase for fish fed diet 4. Lipid and energy efficiency retentions were higher at 0.8:1 CHO:L group. Conclusion: CHO:L ratios around 1.3:1 produced large benefit by best growth performance in the studied hybrid model.